Bracy Clark’s 3D Horse Hoof Model - Boulton, Clare (Veterinary Evidence, 2016)
During the recent reordering of the RCVS headquarters a 6 inch square box was found containing a cardboard model and a folded piece of paper. Further investigation revealed it was something rather exciting – the pasteboard model of a horse’s hoof. Colleagues at the Royal Veterinary College kindly produced a 3D model of the Hoof, which you can view in the interactive video below. You can also read more about Bracy Clark’s model hoof on our Blog. Bracy Clark hoof model c1820 by rcvsknowledge on Sketchfab